Acute effects of mental recovery strategies in simulated air rifle competitions - Loch, F.; Ferrauti, A.; Meyer, T.; Pfeiffer, M.; Kellmann, M. (Frontiers in Sports and Active Living, 2023)
Objectives: The present study aimed to assess the perception and change of mental and physical fatigue and to examine acute effects of mental recovery strategies in air rifle athletes across simulated competition days with two consecutive competition bouts.